2005
DOI: 10.1016/j.bbamem.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the Langmuir monolayer packing of mycolic acids from Mycobacterium tuberculosis

Abstract: Phase diagrams of the Langmuir monolayer of dicyclopropyl alpha mycolic acid (alpha-MA), cyclopropyl methoxy mycolic acid (MeO-MA), and cyclopropyl ketomycolic acids (Keto-MA) from Mycobacterium tuberculosis were obtained by thermodynamic analysis of the surface pressure (pi) vs. average molecular area (A) isotherms at temperatures in the range of 10-46 degrees C. The Langmuir monolayers of MAs were shown to exhibit various phases depending on the temperature (T) and the pi values. In the Langmuir monolayer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 20 publications
10
70
0
1
Order By: Relevance
“…As reported previously, Monte Carlo calculations showed that most of the MAs from the slow-growing mycobacteria tend to form folded conformations, an energetically more stable form, in which the four methylene chain segments are packed together more or less in parallel, hereafter referred to as a 'W-form' conformation (Villeneuve et al, 2005(Villeneuve et al, , 2007(Villeneuve et al, , 2010. However, the thermodynamic studies of the Langmuir monolayers show that different MAs have different conformational behaviours (Villeneuve et al, 2005(Villeneuve et al, , 2007(Villeneuve et al, , 2010.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…As reported previously, Monte Carlo calculations showed that most of the MAs from the slow-growing mycobacteria tend to form folded conformations, an energetically more stable form, in which the four methylene chain segments are packed together more or less in parallel, hereafter referred to as a 'W-form' conformation (Villeneuve et al, 2005(Villeneuve et al, , 2007(Villeneuve et al, , 2010. However, the thermodynamic studies of the Langmuir monolayers show that different MAs have different conformational behaviours (Villeneuve et al, 2005(Villeneuve et al, , 2007(Villeneuve et al, , 2010.…”
Section: Introductionmentioning
confidence: 74%
“…However, the thermodynamic studies of the Langmuir monolayers show that different MAs have different conformational behaviours (Villeneuve et al, 2005(Villeneuve et al, , 2007(Villeneuve et al, , 2010. Thus, non-oxygenated a-MAs take W-form conformations only in a limited area where both temperatures and surface pressures are very low (Villeneuve et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously demonstrated that the regular spacing of functional groups in mycobacterial mycolic acids facilitates folding and packing in monolayer studies (Villeneuve et al, 2005(Villeneuve et al, , 2007. This folding ability is important in allowing mycolic acids to be accommodated within the dimensions of the mycobacterial outer membrane, revealed for the first time by cryo-electron microscopy (Zuber et al, 2008).…”
Section: Discussionmentioning
confidence: 95%